Programmed cell death in plant reproductive development - (:unkn) unknown (Nova Science Publishers, Inc., 2020)
Researchers in last decades have drawn attention to role of programmed cell death (PCD) events in plant growth and development. It has been known that PCD as a fundamental process of cellular organisms regulates the death of cells to complete the functions in plant tissue-organ development, differentiation, and defense against environmental stresses. Although PCD has crucial roles in maintaining both successful vegetative and reproductive development, PCD-related stress researches are more available. In the present review, we focused on the developmentally regulated PCD events originated in plant reproductive development related directly in sustainability of plant population. © 2020 Nova Science Publishers, Inc. All rights reserved.
Keywords: Cell death; Flower development; Pistil; Sex determination; Stamen